Ventricular Interdependence in Patients with Dual-Chamber Pacing: A Doppler Tissue Imaging Study - D'Andrea, Antonello; Caso, Pio; Galderisi, Maurizio; Ducceschi, Valentino; Scherillo, Marino; Sarubbi, Berardo; Mininni, Nicola; Calabro', Raffaele (Echocardiography (Mount Kisco, N.Y.), 2002)
Purpose: To analyze pulsed‐Doppler tissue imaging (DTI) of the right ventricular (RV) tricuspid annulus and left ventricular (LV) mitral annulus in patients paced in the DDD mode at three different pacing modes as compared with healthy subjects, and to investigate possible physiologic interaction between the RV and LV in this subgroup of patients. Methods: We selected a population of 22 subjects with pacemakers (PM) for atrioventricular (AV) block and/or sick sinus syndrome and compared them to 20 healthy subjects. Standard echo Doppler and DTI parameters were measured at baseline (heart rate [HR] 70 beats/min; AV delay 125 msec) and after at least 5 minutes of constant stimulation at two different pacing modes: (1) HR 70 beats/min, AV delay 188 msec, and (2) HR 89 beats/min, AV delay 125 msec. LV stroke volume was obtained by LV outflow Doppler method. Results: In the PM group, RV and LV annulus exhibited significantly higher peak systolic (Sm) and early (Em) diastolic wall velocities than controls. In the PM population, LV stroke volume was strongly associated to RV Em peak velocity (r = 0.83; P < 0.00001) and RV Sm peak velocity (r = 0.81; P < 0.0001). These associations between LV stroke volume and RV DTI parameters remained significant even after increase of HR and AV delay in the pacing modalities. Moreover, univariate relations were found in the PM group between DTI indexes of RV tricuspid annulus and the homologous indexes of LV mitral annulus. In a multiple linear regression analysis, both RV Em (P < 0.001) and RV Sm (P < 0.001) were related independently to LV stroke volume (cumulative R2= 0.85, P < 0.00001). Conclusions: Our findings suggest the usefulness of pulsed‐DTI to display physiologic ventricular interaction in patients with PM. Therefore, DTI may be taken into account as a valuable supporting tool to predict LV systolic performance and to select the most appropriate pacing mode in individual PM patients.